El bien jurídico de la vida y el principio de proporcionalidad en los delitos culposos de tránsito. - Chávez Amaguaya, Elías Alexander (2025)
This research analyzes the principle of proportionality and the protection of the legal right to life within the framework of negligent traffic offenses, as established in Ecuador's Comprehensive Organic Criminal Code (COIP). It begins with the recognition of life as a fundamental right protected by the Constitution of the Republic of Ecuador, whose safeguard must be a priority in all criminal policy. The study identifies a normative contradiction in the application of penalties, as the COIP imposes harsher penalties for certain traffic-related injuries than for negligent homicide, which implies a devaluation of the legal right to life compared to physical integrity. Through a legal-dogmatic approach and a methodology based on normative, jurisprudential, and doctrinal analysis, complemented by statistical data, the study evaluates whether current penalties meet the criteria of justice and proportionality. The research reveals that the penalty for negligent homicide (1 to 3 years) is lower than that for certain serious injuries (up to 3 years and 9 months), violating the principle of proportionality enshrined in Article 76 of the Constitution. The study concludes that this normative inconsistency creates legal uncertainty, undermines the preventive function of criminal law, and weakens the protection of the legal right to life. A legislative reform is recommended to correct the disproportionate penalties and ensure a criminal response that is consistent with the severity of the offenses and respectful of fundamental rights.